2018
DOI: 10.1167/iovs.17-23532
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Photoreceptors and RPE Cells Damage by Intravenous Sodium Iodate in Mice Is Related to Macrophage Accumulation

Abstract: The NaIO3-induced retinal damage was reversible at low concentrations but permanent at high concentrations of NaIO3. The accumulation of macrophages around the RPE cells caused the photoreceptor cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 48 publications
(58 reference statements)
9
62
0
Order By: Relevance
“…Of note, in our present study transcription levels of properdin-treated cells were always reversed after 24 h compared to 4 h. Our assumption of a tightly regulated time-dependent complement expression profile in the RPE and retina was further supported by others showing that complement inhibiting components peaked simultaneously with photoreceptor apoptosis after light-induced retinal damage in rats [ 83 ]. A similar effect was observed for expression of AMD-related genes and cytokines in mice after intravenous sodium iodate injection [ 84 ].…”
Section: Discussionsupporting
confidence: 74%
“…Of note, in our present study transcription levels of properdin-treated cells were always reversed after 24 h compared to 4 h. Our assumption of a tightly regulated time-dependent complement expression profile in the RPE and retina was further supported by others showing that complement inhibiting components peaked simultaneously with photoreceptor apoptosis after light-induced retinal damage in rats [ 83 ]. A similar effect was observed for expression of AMD-related genes and cytokines in mice after intravenous sodium iodate injection [ 84 ].…”
Section: Discussionsupporting
confidence: 74%
“…We next performed an intraperitoneal injection of NaIO 3 to cause retinal fibrosis secondary to RPE damage and photoreceptor degeneration in mice 51 . Normal RPE cells strongly expressed RPE65 (Figure 8 A) along with a regular alignment of photoreceptor apical processes (Figure 8 B).…”
Section: Resultsmentioning
confidence: 99%
“…We used a mouse model of Müller cell gliosis caused by intraperitoneal NaIO 3 to study changes in Notch and TGFβ signaling and tested the effects of intravitreal injection of RO4929097 on Müller cell gliosis. NaIO 3 is a chemical oxidizing agent that was reported to primarily damage the RPE, leading to subsequent photoreceptor degeneration and alterations in retinal structures including Müller cell gliosis 51 , 59 - 61 . Müller cell gliosis has been found on the surface of the retina and in the subretinal space in a previous study using the NaIO 3 -induced retinal damage model in rabbits 61 .…”
Section: Discussionmentioning
confidence: 99%
“…The implication for our data is that TLR2 deficiency may result in reduced macrophage and microglial infiltration to the retina in response to oxidative stress. A recent report has demonstrated that photoreceptor cell death in the NaIO 3 model is correlative with activated macrophage accumulation in the outer retina after RPE degeneration (Moriguchi et al, 2018). We next assessed the extent to which absence of TLR2 might influence macrophage/microglial cell migration into the outer retina, in response to oxidative stress.…”
Section: Tlr2 Deficiency Delays Naio 3 -Induced Iba1+mentioning
confidence: 99%